Growth performance, sex ratio, feed utilization, and survival of Oreochromis hybrids. Issue 1 (2nd January 2023) - Nzohabonayo, Elysée; Kang'ombe, Jeremiah; Manyala, Julius; Kassam, Daud
ABSTRACT: An experiment was conducted to evaluate the growth performance of hybrids from a diallel 3 × 3 crossing of Oreochromis karongae, O. shiranus, and O. mossambicus . Fingerlings of 3.47 ± 0.04 g were stocked at 5 fish m −2 in nine treatments replicated twice. Final weights were significantly different (P < 0.05) among treatments whereby hybrids from female O. karongae and male O. mossambicus registered higher values (48.48 ± 0.58 g) than other crosses. Hybrids from female O. karongae significantly (P < 0.05) performed well in terms of AFCR as they registered lower values (<2). The proportion of males varied between 65% and 90% in hybrids; survival ranged from 62.5% to 100%. Heterosis in hybrids from crosses with female O. karongae ranged from10.72 to 33.25. The results suggest that hybrids from crosses with female O. karongae may be suitable candidates for commercial fish farming as they have superiority of the most productive performance traits.